YouTube coverage of COVID-19 vaccine development: implications for awareness and uptake - Corey H. Basch; Grace C. Hillyer; Emily A. Zagnit; Charles E. Basch (Taylor & Francis Group, 2020)
This study examined 100 widely viewed YouTube videos on COVID-19 vaccination. Information such as length, format, upload source, content, and cumulative views was coded. As of April 6, 2020, the videos were viewed >33 million times. Almost 75% were uploaded by news sources (garnering >20 million views). While only 16% were uploaded by consumers, these videos garnered over 25% of cumulative views (n = 8,581,186 views). The majority of videos mentioned the vaccine manufacturing process (61.0%) and 45.0% speculated on the amount of time needed to have a vaccine ready for use, which most often was thought to be 1-2 years. Even once the biological and technical aspects of vaccine development and manufacturing are accomplished, the benefits conferred on population health will also depend on public willingness to be vaccinated. Ongoing tracking of YouTube is needed to identify what is communicated about vaccines for COVID-19. To the extent that public health officials learn how to create videos about the safety and effectiveness of a COVID-19 vaccine, which attract viewers, this could help increase awareness and interest about vaccination and help individuals make an informed decision about vaccine uptake.